Strengthening the Profile of Pancasila Students Through Religious Activities at Bahrul Ulum Tambakberas Islamic Boarding School - Muhammad Khizbullah; Muhamad Khoirur Roziqin; Chusnul Chotimah (APPLICATION: Applied science in Learning Research, 2026)
This study aims to describe the implementation of religious activities, analyze their contribution to strengthening the Profil Pelajar Pancasila (P5), and identify supporting and inhibiting factors in fostering these values at Bahrul Ulum Tambakberas Islamic Boarding School. The subjects of this study consisted of 8 students and 3 teachers (ustadz/ustadzah) who were directly involved in the boarding school’s religious activities. Purposive sampling was used to select participants based on criteria of active student participation in religious activities and teachers supervising these activities. This research employed a qualitative approach with a descriptive case study design. Data were collected through observation, interviews, and documentation, and analyzed using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that religious activities at the boarding school are carried out in a structured manner through daily, weekly, and seasonal activities, such as congregational prayers, Quran recitation, study of classical Islamic texts, istighotsah, tahlil, manaqib, maulid celebrations, and social activities such as communal work. These activities contribute to strengthening students’ religiosity, cooperation, independence, discipline, tolerance, and responsibility, which align with the six dimensions of the Profil Pelajar Pancasila. Supporting factors include the exemplary role of the kyai and teachers, the boarding school’s religious culture, and an integrated educational system. In contrast, inhibiting factors include differences in students’ understanding of Pancasila values and a densely packed activity schedule.